Ultrasensitive and Highly Stretchable Multiple-Crosslinked Ionic Hydrogel Sensors with Long-Term Stability - Yu, Jin‑Young; Moon, Seung Eon; Kim, Jeong Hun; Kang, Seong Min (Nano-Micro Letters, 2023)
Flexible hydrogels are receiving significant attention for their application in wearable sensors. However, most hydrogel materials exhibit weak and one-time adhesion, low sensitivity, ice crystallization, water evaporation, and poor self-recovery, thereby limiting their application as sensors. These issues are only partly addressed in previous studies. Herein, a multiple-crosslinked poly(2-(methacryloyloxy)ethyl)dimethyl-(3-sulfopropyl)ammonium hydroxide-co-acrylamide) (P(SBMA-co-AAm)) multifunctional hydrogel is prepared via a one-pot synthesis method to overcome the aforementioned limitations. Specifically, ions, glycerol, and 2-(methacryloyloxy)ethyl)dimethyl-(3-sulfopropyl)ammonium hydroxide are incorporated to reduce the freezing point and improve the moisture retention ability. The proposed hydrogel is superior to existing hydrogels because it exhibits good stretchability (a strain of 2900%), self-healing properties, and transparency through effective energy dissipation in its dynamic crosslinked network. Further, 2-(methacryloyloxy)ethyl)dimethyl-(3-sulfopropyl)ammonium hydroxide as a zwitterion monomer results in an excellent gauge factor of 43.4 at strains of 1300–1600% by improving the ion transportability and achieving a strong adhesion of 20.9 kPa owing to the dipole–dipole moment. The proposed hydrogel is promising for next-generation biomedical applications, such as soft robots, and health monitoring. Highlights: 1 A multiple-crosslinked poly(2-(methacryloyloxy)ethyl)dimethyl-(3-sulfopropyl)ammonium hydroxide-co-acrylamide multifunctional hydrogel was prepared via a one-pot synthesis method. 2 The proposed hydrogel exhibits water retention, antifreeze properties, self-healing, and transparency as well as improved strength, good adhesiveness, and a high gauge factor.